Revisiting Tourism Flows to the Caribbean : What is Driving Arrivals? - Laframboise, Nicole (IMF Working Papers; Working Paper ;, 2014)
The Caribbean share of the global tourism market has been declining. This study examines what is driving tourism flows. It estimates the determinants of tourism and explores variations based on sample differences, and also constructs a static nominal price comparison index. The paper finds that: (i) tourism arrivals and expenditure are sensitive to both price and income factors in source markets; (ii) price and income elasticities of tourism have declined since 2008; (iii) price elasticity is statistically insignificant for 'high-end' destinations; and (iv) the nominal cost of an average one week beach holiday in the Caribbean is higher than in other beach destinations around the world. These results point to the need for structural reforms to raise product quality, cost reduction or containment in 'low-end' destinations, including possibly via exchange rates, and an adjustment in aggregate consumption to adapt to the implications of a lower contribution to GDP from tourism.